2016
DOI: 10.1007/s00248-016-0874-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Fungal Diversity in Citrus Leaves with Greasy Spot Disease Symptoms

Abstract: Citrus greasy spot (CGS) is a disease of citrus with worldwide distribution and recent surveys have revealed a high level of incidence and severity of symptoms of the disease in Sicily, southern Italy. Although Mycosphaerel la citri (anamorph Zasmidium citri-griseum) and other related species are generally considered as causal agents, the etiology of CGS is still unclear. Here, we report the use of an amplicon metagenomic approach to investigate the fungal communities on citrus leaves symptomatic or asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…The consensus of the olive community composition described herein, including the proportion of the fungal taxa at all the taxonomical levels (from phyla to genera) is in strong agreement with the previous description of the olive fungal community; being dominated by fungal genera such as Aureobasidium , Cladosporium , and Alternaria (14). The stability of the olive fungal community in the investigated samples in the present and in a previous study (14), and how they differ remarkably from other hosts (21) (30) (21), confirms that the microbial community is determined primarily by its host identity. Interestingly, non-pathogenic fungal species such as Aureobasidium pullulans were largely prevalent in all localities.…”
Section: Discussionsupporting
confidence: 84%
“…The consensus of the olive community composition described herein, including the proportion of the fungal taxa at all the taxonomical levels (from phyla to genera) is in strong agreement with the previous description of the olive fungal community; being dominated by fungal genera such as Aureobasidium , Cladosporium , and Alternaria (14). The stability of the olive fungal community in the investigated samples in the present and in a previous study (14), and how they differ remarkably from other hosts (21) (30) (21), confirms that the microbial community is determined primarily by its host identity. Interestingly, non-pathogenic fungal species such as Aureobasidium pullulans were largely prevalent in all localities.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, none of the detected sequences clustered with Z . citri-griseum or allied species previously associated with citrus greasy spot in other regions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…was associated with the disease [ 10 , 11 ]. Furthermore, recent metagenomic studies in Sicily indicated that the family Mycosphaerellaceae was the most abundant in leaves with greasy spot symptoms [ 12 ]. Symptoms of citrus greasy spot have also been observed in sweet orange in Egypt, but in this case the species Z .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the fungal community using an amplicon metagenomic approach has revealed that Mycosphaerellaceae were the dominant group of fungi, in both symptomatic and asymptomatic leaves, and were represented by the genera Ramularia, Mycosphaerella and Septoria, with about 44, 2.5 and 1.7% of the total detected sequences [39]. The most abundant sequence type was associated to Ramularia brunnea, a species originally described to cause leaf spot in a plant of the family Asteraceae.…”
Section: Citrus Pathologymentioning
confidence: 99%